Use of Endodontic Imaging Modalities in Forensic Identifications - Uzma Zaheen, Khurram Nadeem, Shaiqa Ramzan, Mansoora Mirza, Haroon Anwar Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Forensic odontology has a advance role in identifying a deceased person using dental records. Because of the growing trend of litigation around the world, precise recording of clinical dental operations has become increasingly necessary. Objective: To see the endodontic obturation radiographs have a hidden function in identification. Study Design: Cross-sectional study. Place and Duration of Study: Dental OPD, Central Park, Lahore and Private Clinics of Lahore from 1st March 2022 to 31st August 2022. Methods: From the digital X-ray system's data bank, 30 periapical radiographs of patients who had endodontic treatment of the mandibular left (first molars with three canals) were randomly selected. The ante-mortem data "Set 1" consisted of post-operative radiographs. From the thirty radiographs, ten were reprinted, labelled (A-J), and deemed post-mortem data "Set 2."This "Set 2" post-mortem group of 10 radiographs would be compared to the "Set 1" ante-mortem group of 30 radiographs. Ten dentally educated persons would examine these two sets of radiographs. Each examiner was given thirty radiographs from "Set 1" and ten radiographs from "Set 2," with the task of matching the individual post-mortem radiographs ("Set 2") with the ante-mortem radiographs ("Set 1"). Results: Thirty four examiners had a 100% success rate, 4 examiners had a 97.5% success rate (1 mismatch), and 2 examiners had a 95% success rate (2 mismatches). Conclusion: On the off chance that after death radiographs are precise duplicates of endodontic obturated radiographs, the obturation's novel shape can be taken advantage of for forensic ID. Keywords: Forensic odontology, Endodontic obturated radiographs